The effect of maceration on the organoleptic properties of ginger-based functional beverages - Syirril Ihromi; Dina Soes Putri; Marianah Marianah (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
Functional beverages represent a category of beverages that provide both sensory satisfaction and health benefits. In Indonesia, functional beverages such as jamu or herbal drinks are typically formulated from one or more combinations of spices or herbs. One frequently utilized herb is white ginger. In this study, the herbal beverage was formulated using a combination of white ginger, lemongrass, cinnamon, cloves, and pandan leaves. The objective of this study was to determine the effect of maceration on the sensory properties of ginger-based functional beverages. The maceration process was subdivided into three treatments: soaking for 0 (T1), 6 (T2), and 12 (T3) hours. The organoleptic test results were subjected to statistical analysis using Analysis of Variance at a confidence level of 5%. Preliminary organoleptic testing results indicate that the maceration process exerts a significant influence on the sensory characteristics of the functional beverage under investigation. Specifically, an increase in maceration time was associated with elevated color and turbidity scores, while concurrently resulting in a reduction in taste scores. In conclusion, based on the preferences of the panel, treatment T3 was most preferred for color and turbidity, while T1 was most preferred for its taste.